Polar extracts from (Tunisian) Acacia salicina Lindl. Study of the antimicrobial and antigenotoxic activities - Boubaker Jihed; Mansour Hedi; Ghedira Kamel; Ghedira Leila (BMC, 2012)
Abstract Background Methanolic, aqueous and Total Oligomer Flavonoids (TOF)-enriched extracts obtained from the leaves of Acacia salicina 'Lindl.' were investigated for antibacterial, antimutagenic and antioxidant activities. Methods The antimicrobial activity was tested on the Gram positive and Gram negative reference bacterial strains. The Mutagenic and antimutagenic activities against direct acting mutagens, methylmethane sulfonate (MMS) and 4-nitro-o-phenylenediamine (NOPD), and indirect acting mutagens, 2-aminoanthracene (2-AA) and benzo[a]pyrene (B(a)P) were performed with S. typhimurium TA102 and TA98 assay systems. In addition, the enzymatic and nonenzymatic methods were employed to evaluate the anti-oxidative effects of the tested extracts. Results A significant effect against the Gram positive and Gram negative reference bacterial strains was observed with all the extracts. The mutagenic and antimutagenic studies revealed that all the extracts decreased the mutagenicity induced by B(a)P (7.5 μg/plate), 2-AA (5 μg/plate), MMS (1.3 mg/plate) and NOPD (10 μg/plate). Likewise, all the extracts showed an important free radical scavenging activity towards the superoxide anion generated by the xanthine/xanthine oxidase assay system, as well as high Trolox Equivalent Antioxidant Capacity (TEAC), against the 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS)+• radical. TOF-enriched extract exhibited the highest protective effect against free radicals, direct acting-mutagen and metabolically activated S9-dependent mutagens. Conclusions The present study indicates that the extracts from A. salicina leaves are a significant source of compounds with the antimutagenic and antioxidant activities, and this may be useful for developing potential chemopreventive substances.